The effect of challenge-based gamification on learning: An experiment in the context of statistics education - Legaki, Nikoletta-Zampeta; Xi, Nannan; Hamari, Juho; Karpouzis, Kostas; Assimakopoulos, Vassilios (International journal of human-computer studies, 2020)
•We investigated the impact of gamification on learning in statistics education.•We examined challenge-based gamification (points, levels, challenges, leaderboard).•We ran a 2 (read yes | no) x 2 (gamification yes | no) between-subject experiment.•Gamification had a positive impact on learning.•Effect was larger for females and Engineering students versus Business School students. Gamification is increasingly employed in learning environments as a way to increase student motivation and consequent learning outcomes. However, while the research on the effectiveness of gamification in the context of education has been growing, there are blind spots regarding which types of gamification may be suitable for different educational contexts. This study investigates the effects of the challenge-based gamification on learning in the area of statistics education. We developed a gamification approach, called Horses for Courses, which is composed of main game design patterns related to the challenge-based gamification; points, levels, challenges and a leaderboard. Having conducted a 2 (read: yes vs. no) x 2 (gamification: yes vs. no) between-subject experiment, we present a quantitative analysis of the performance of 365 students from two different academic majors: Electrical and Computer Engineering (n=279), and Business Administration (n=86). The results of our experiments show that the challenge-based gamification had a positive impact on student learning compared to traditional teaching methods (compared to having no treatment and treatment involving reading exercises). The effect was larger for females or for students at the School of Electrical and Computer Engineering.